2017
DOI: 10.1080/01635581.2017.1359309
|View full text |Cite
|
Sign up to set email alerts
|

Dual Effects of Resveratrol on Cell Death and Proliferation of Colon Cancer Cells

Abstract: Colorectal cancer remains a main cause of deaths worldwide, and novel agents are being searched to treat this disease. Polyphenols have emerged as promising therapeutic tools in cancer. Resveratrol (3,5,4'-trihydoxy-trans-stilbene) induces cell death in different tumor cell lines, and it also stimulates the proliferation of specific breast and prostate cancer cell lines. Here, we studied the impact of resveratrol over a 100-fold concentration range on cell death and proliferation of HT-29 colorectal adenocarci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 29 publications
1
34
0
Order By: Relevance
“…Overall, the tested compound exerted a biphasic effect on normal Vero cells in terms of proliferation and cytotoxicity. Similar effects of polyphenolic compounds were also signaled on other cell lines, the biphasic behavior being dose-dependent [ 32 ].…”
Section: Discussionmentioning
confidence: 65%
“…Overall, the tested compound exerted a biphasic effect on normal Vero cells in terms of proliferation and cytotoxicity. Similar effects of polyphenolic compounds were also signaled on other cell lines, the biphasic behavior being dose-dependent [ 32 ].…”
Section: Discussionmentioning
confidence: 65%
“…It is worth mentioning, however, that although SIRT1 stabilization provided similar survival benefit as targeting NOX4 (Fig. S5 D), some studies have suggested that SIRT1 modulation may have potential therapeutic limitations, due in part to a prooxidant role or tumor growth-inducing properties (de la Lastra and Villegas, 2007;San Hipólito-Luengo et al, 2017). Depending on the cellular context, SIRT1 can act either as a tumor suppressor or as a tumor promoter and may have different signaling targets in different cell types (Chen et al, 2005;Yeung et al, 2004).…”
Section: Discussionmentioning
confidence: 94%
“…At concentrations, 1-10 µM RES increased about 2-fold a number of cells whereas at 50 µM and 100 µM, the percentage of necrotic and apoptotic cells was reduced by 76% and 90%, respectively. RES-induced cytotoxicity was associated with NADP oxidase activation and increased level of histone GH2AX, a marker of DNA damage [50].…”
Section: Resveratrolmentioning
confidence: 98%